Carbon Sequestration Potential in Piple Pokhara Community Forest: Implications for Climate Change Mitigation - Rai, Nitesh; Budhamagar, Rima Kumari; Bidari, Manish; Paudel, Kedar (FORESTRY: Journal of Institute of Forestry, Nepal, 2024)
Forests are considered a cost-effective way to reduce global CO2 emissions, yet the viability of community forest management for climate change mitigation remains underexplored. This study evaluates the carbon sequestration potential of the Piple Pokhara Community Forest, which spans 209.09 hectares and contains diverse tree species like Shorea robusta and Schima wallichii. Using stratified random sampling, 42 circular plots were established for carbon pool measurements. The findings reveal significant carbon stocks, with a total of 138.94 tons per hectare. Converted to CO2 equivalent, the forest sequesters 509.91 tons of CO2 per hectare. Shorea robusta is the dominant species, contributing 75.93% of the total carbon stock. The highest carbon reserves were in trees with a diameter at breast height (DBH) over 30 cm and heights between 15.1 and 20 meters. This study underscores the Piple Pokhara Community Forest's considerable carbon sequestration potential and suggests economic benefits through carbon trading. It highlights the forest's role in climate change mitigation and its benefits for both forest conservation and community well-being.